A Direct Damage Stability Calculation Method for an Onboard Loading Computer - Chunlei Liu; Lianzhong Huang; Xiaofeng Sun; Yong Yin (Journal of Marine Science and Engineering, 2022)
The stability analysis of a damaged ship is both important and challenging for an onboard loading computer. To help ship operators make reasonable decisions, a Simplified Newton Iteration Method is proposed to calculate damage stability in real time based on 3D geometric models of the ship. A 7500-dead-weight-tonnage (DWT) asphalt tanker, “TAI HUA WAN”, is used to illustrate the effectiveness of the proposed approach. The damage stability results of 18 typical loading conditions are calculated. The average error of righting lever GZ is 0.002 m, and the average number of iterations is nine. The calculation results show that the proposed method is simple, with real-time processes, robustness, accuracy, and certain practical value for engineering. Furthermore, based on the proposed method, a loading computer, “SMART LOAD”, has been developed and approved by LR, DNV, CCS, ABS, NK and the BV Classification Society and has been installed on more than 150 vessels worldwide.